Streptomyces nucleases - Joshi, Amruta Pramod; Deshmukh, Sumedha Sharad (Critical Reviews in Microbiology, 2011)
Streptomyces nucleases are widely distributed and multifunctional enzymes acting on both DNA and RNA. They occur extra as well as intracellularly and can be classified under sugar specific and sugar non-specific nucleases. Nucleases play different roles like analytical, biological, and nutritional. They are also used in programmed cell death. Although more than 20 nucleases are reported to date, very little information is available regarding their structure-function relationship, active site based sequence homology, and the probable mechanism of action. This review describes the history, occurrence, localization, production, purification, properties, and applications of Streptomyces nucleases.
Keywords: Applications; Endonuclease; extracellular; production; Purification; Substrate specificity